Implementation of Islamic Marketing Strategies and Its Impact on Consumer Behavior, a Literature Review - Mamik Setiyorini; Vanessa Ghaffar; Hilda Monoarfa (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The purpose of this article is to examine the theory and implementation of Islamic marketing management globally and the factors shaping consumer behavior. The source material is derived from a review of marketing management books and international journals, which were thoroughly reviewed and analyzed to obtain analytical results that can benefit users in this field. The method used in this study is qualitative research, using an inductive analysis approach and a literature review. The research was conducted using theoretical analysis from books and an analysis of 25 previous research articles from the Emerald Insight platform from 2018 to 2024.The analysis results provide a scope of Islamic marketing strategy and descriptive analysis of Islamic consumer behavior, implemented Islamic marketing strategies, and consumer behavior of Islamic products/services users in various countries from 2018 to 2024. This study provides material and references for further research, including theoretical studies, indicators, and variables on Islamic marketing strategy and consumer behavior of Islamic products/services users. Limitations of this study include the lack of an in-depth examination of the use of technology in Islamic marketing strategies. The implications of this research can be used by management in formulating Islamic marketing strategies and managerial decision making in the marketing sector.